Electrodynamic context of magnetopause dynamics observed by magnetospheric multiscale. Issue 12 (21st June 2016) - Anderson, Brian J.; Russell, Christopher T.; Strangeway, Robert J.; Plaschke, Ferdinand; Magnes, Werner; Fischer, David; Korth, Haje; Merkin, Viacheslav G.; Barnes, Robin J.; Waters, Colin L.; Cohen, Ian J.; Westlake, Joseph H.; et al.
Abstract: Magnetopause observations by Magnetospheric Multiscale (MMS) and Birkeland currents observed by the Active Magnetosphere and Planetary Electrodynamics Response Experiment are used to relate magnetopause encounters to ionospheric electrodynamics. MMS magnetopause crossings on 15 August and 19 September 2015 occurred earthward of expectations due to solar wind ram pressure alone and coincided with equatorward expansion of the Birkeland currents. Magnetopause erosion, consistent with expansion of the polar cap, contributed to the magnetopause crossings. The ionospheric projections of MMS during the events and at times of the magnetopause crossings indicate that MMS observations are related to the main path of flux transport in one case but not in a second. The analysis provides a way to routinely relate in situ observations to the context of in situ convection and flux transport. Key Points: A method is presented to routinely assess the ionospheric electrodynamic context of MMS magnetopause observations Two magnetopause crossings examined require erosion in addition to compression consistent with observed polar cap expansion The convection implies that MMS observations are related to the main path of flux transport in the first case but not in the second